NEMÁTODOS EN AVES SILVESTRES DEL ÁREA DE CONSERVACIÓN PRIVADA “GOTAS DE AGUA” JAÉN, CAJAMARCA, PERÚ - Hon Yi, Enrique Octavio (2013)
The purpose of this study was to determine the presence of nematodes in wild birds the private conservation area of Gotas de Agua in Jaén, Cajamarca, Peru. The birds were collected using mist nets or firearms. The search of endoparasites was performed in internal organs (heart, liver, gizzard, air cavities) and eyes. Nematodes were preserved in 70% alcohol. A total of 159 birds belonging to 45 different species were collected, of which only five species were parasitized, three of them, Myiarchus phaeocephalus (Tyrannidae) with Diplotriaena sp. Myiarchus tyrannulus (Tyrannidae) with Diplotriaena sp. D. delirae and D. zederi, Pheucticus chrysogaster (Corvidae) with D. Americana, Cyanocorax yncas (Corvidae) with Thelazia aff. longicaudata and Caprimulgus anthonyi (Caprimulgidae) with Aprocta sp. 121 helminthes were found in the genera Diplotriaena , Thelazia and Aprocta with a total prevalence of 6.91 % , mean abundance of 0.76 and an average total intensity of 11. Diplotriaena americana in Pheucticus chrysogaster, D. delirae and D. zederi in Myiarchus tyrannulus are recorded for the first time in Peru. In addition, Cyanocorax yncas is recorded for the first time as the definitive host of T. aff. longicaudata in Peru, and Caprimulgus anthonyi is recorded for the first time as a host of Aprocta sp. in Peru. There was no relationship between parasitism and sex, diet, habitat and family of all birds examined, although a relationship with the weight of the birds was observed.